2019
DOI: 10.1111/jnu.12523
|View full text |Cite
|
Sign up to set email alerts
|

Role of Coping Styles in the Relationship Between Nurses’ Work Stress and Well‐Being Across Career

Abstract: Objectives: This study examines the mediating role of stress coping stylesproblem-focused coping and emotion-focused coping-on the relationship between work stress and psychological well-being in clinical nurses according to career experience. Methods: A cross-sectional survey design was used. Data were collected from February to March 2016. The study population was composed of 399 nurses working at two university hospitals with over 500 beds located in Seoul and Gyeonggi-do in South Korea. Self-report questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The results of the present study demonstrated that low work-related stress was sequentially associated with increased professional identity first and then with increased PsyCap, which in turn was related to the increase in work-related wellbeing. A large number of studies have shown that work-related stress has a negative impact on work-related wellbeing (Sun et al, 2013;Jang et al, 2019). In addition, according to a study of nurses by Wan, occupational identity was positively correlated with PsyCap (Sun et al, 2012;Wan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study demonstrated that low work-related stress was sequentially associated with increased professional identity first and then with increased PsyCap, which in turn was related to the increase in work-related wellbeing. A large number of studies have shown that work-related stress has a negative impact on work-related wellbeing (Sun et al, 2013;Jang et al, 2019). In addition, according to a study of nurses by Wan, occupational identity was positively correlated with PsyCap (Sun et al, 2012;Wan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…32 Studies have concluded that individuals with a positive coping style are less likely to face psychological distress. 26,78,79 Adopting effective coping methods may play a crucial role in reducing occupational-related psychological distress among nurses.…”
mentioning
confidence: 99%
“…Employees may use problem or emotion-focused strategies to replenish their mental and physical resources caused by emotional strain of performing emotional labour (Demerouti, 2015). Problem-focused strategies refer to strategies that enable employees to directly tackle or combat the cause of the stress (D'Souza et al, 2009;Jang et al, 2019). These strategies enable individuals to acquire and maintain sufficient resource reservoirs to act early when signs of a problem arise (Hobfoll, 2001).…”
Section: Emotion Events Performances and Responsesmentioning
confidence: 99%